Cruel intent - Jance, Judith A., 1944- (Simon & Schuster, 2008)
Ali Reynolds doesn't go looking for trouble - but trouble comes looking for her when the battered, bloodstained body of Morgan Forester is discovered by her twin daughters. For the prime suspect, Morgan's husband, is the contractor Ali has hired to help re-design her home. Bryan Forester swears he had nothing to do with the killing - but no one, including Ali's boyfriend, Homicide Detective Dave Holman, believes him. Was Morgan's death the result of a domestic dispute that turned violent - or is her murder part of something far more sinister? In her determination to prove Bryan's innocence, Ali finds she has unwittingly entered a deadly game of cyber hide-and-seek with a ruthless killer.